TRANSFORMASI DIGITAL: PELUANG BARU BAGI KEUANGAN SYARIAH DI INDONESIA - Rahmawati, Eka; Ningsih, Arfita; Nabila, Dita Dwi; Lestari, Ayu Puji; Fatmawati, F (Pusat Riset dan Publikasi, 2024)
Digitalization has become a major driving force in various sectors, including the financial sector. Syariah financial in Indonesia, which has the largest Muslim population in the world, has benefited greatly from this digital transformation. This article discusses the impact of digitalization on syariah financial in Indonesia, the opportunities it offers, and the challenges faced in adopting digital technologies. Through e-banking, mobile banking, syariah financial, and the integration of big data and artificial intelligence, syariah financial can increase financial inclusion, operational efficiency, attract the younger generation, and drive product and service innovation. However, challenges such as the digital divide, data security, infrastructure readiness, and supporting regulations still need to be addressed. With the right strategy, digitalization has great potential to strengthen syariah financial in Indonesia.